LEGAL ANALYSIS OF CRIMINALIZATION BY LAW ENFORCEMENT OFFICERS AGAINST VICTIMS OF DRUG ABUSE FROM THE PERSPECTIVE OF PROGRESSIVE LAW IN INDONESIA - Putra, M. Indra Eka; Gunarto, Gunarto (Jurnal Hukum Khaira Ummah, 2024)
Drug trafficking in Indonesia is legal for medical purposes but illegal for recreational use. Drug abuse is a serious problem, but drug abusers still have human rights, including the right to rehabilitation. This study examines the criminalization of drug abuse, especially by law enforcement officials, and the potential for a more balanced approach that combines legal and health perspectives. Using sociological juridical methods, the study analyzes the legal framework, law enforcement practices, and their impact on drug users. The findings highlight the need for a more in-depth approach that prioritizes rehabilitation and treatment alongside criminal sanctions. This approach would better address the root causes of drug abuse and promote effective prevention and eradication strategies.